Cloning gene encoding transcription factor DREB1 for regulating abiotic stress of L14 peanut variety - Anh, Trần Linh; Tiến, Nguyễn Quang Đức (Hue University Journal of Science: Natural Science, 2023)
Peanut (Arachis hypogaea L.) is an essential short-term industrial crop, producing most of the world’s vegetable oil and protein. Peanuts are commonly used as human and animal food, as well as raw materials in a variety of industries. Peanuts are widely grown in tropical and subtropical regions, with Asia being the world’s largest peanut-growing area, accounting for more than 67% of the total peanut production. Numerous studies have shown that identifying genes related to drought tolerance in plants is critical for the selection or improvement of drought-tolerant varieties to reduce the risk of damage caused by dry weather conditions. The transcription factor DREB (Dehydration-Responsive Element Binding Protein) has been shown to play a significant role in plant tolerance to drought stress responses. The gene encoding the transcription factor DREB1 in response to the drought-tolerant peanut variety L14 was isolated, sequenced, and analyzed in this study. The DREB1’s cDNA sequence is 1050 nucleotides long and encodes 349 amino acids. The findings of the study reveal that the DREB1 gene in the L14 peanut variety differs from the published corresponding gene sequence from another peanut by 0.48%. The AhL14_DREB1 gene sequence is the basic information to improve the drought tolerance of local peanut varieties in further studies.